2019
DOI: 10.1016/j.proci.2018.06.090
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the electrical properties and nanostructure of soot particles in a laminar inverse diffusion flame

Abstract: This is a repository copy of Relationships between the electrical properties and nanostructure of soot particles in a laminar inverse diffusion flame.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The electrical properties are strongly dependent on the nanostructure of soot particles. In our previous studies, the crystallite width was found to have a positive correlation with electrical properties for soot samples, and the interlayer distance exhibited a close negative relationship with the electrical properties [12]. Grob et al [13] revealed that a loss of the crystalline order led to an increasing amorphization in soot, which caused a decrease in electrical conductivity.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…The electrical properties are strongly dependent on the nanostructure of soot particles. In our previous studies, the crystallite width was found to have a positive correlation with electrical properties for soot samples, and the interlayer distance exhibited a close negative relationship with the electrical properties [12]. Grob et al [13] revealed that a loss of the crystalline order led to an increasing amorphization in soot, which caused a decrease in electrical conductivity.…”
Section: Introductionmentioning
confidence: 83%
“…2. Further details on the diffusion flame burner system are reported in our previous study [12]. A thermophoretic sampling technique based on the thermophoresis principle was employed to quickly obtain the soot particles at varying HABs for the analysis of atomic force microscopy (AFM).…”
Section: Burner and Sampling Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to improve the electrical conductivity, the authors add steel fibers and microfibers [43][44][45][46], steel shavings [43,45], graphite powder [47,48], graphite and carbon fibers (CF) [49][50][51] and microfibers (CMF) [19,44,[52][53][54][55][56][57][58], carbon nanofibers (CNF) [59], carbon nanotubes (CNT) [11,52,[60][61][62][63][64][65][66], graphene [67,68], anthracite [69] and carbon black powder [70,71] into cementitious composites. Liu [72] focuses on the electric conductivity of soot. Some authors explore the effects of adding ash on electric conductivity [73].…”
Section: Introductionmentioning
confidence: 99%